Integration of Artificial Intelligence in Law for Training Development Course in the Army Cadet Program - Wiwatthanapongpun, Pemika (Interdisciplinary Academic and Research Journal, 2025)
Background and Aims: This independent study aims to (1) investigate the concepts of artificial intelligence and (2) integrate artificial intelligence in the Law for Training Development Course in the Non-Commissioned Officer Student Program through documentary research and related research, analyzing and presenting the results according to the research objectives. Methodology: This study is a literature review study related to the concepts of applying artificial intelligence in the content analysis of the Non-Commissioned Officer Student Program and the descriptive presentation according to the important issues. Results: The findings revealed that a law course was one of the courses specified in the training of the Non-Commissioned Officer Student Program, consisting of Introduction to Law, Criminal Law 1, Criminal Law 2, Criminal Procedure Law, Police Affair Regulations Regarding Cases, and Acts with Criminal Punishment. However, the course still lacked the integration of artificial intelligence in instructional management, leading to inefficiency in strengthening in-depth understanding and applying knowledge in real-life situations, as well as developing necessary skills for analyzing legal matters and making decisions in complex situations, which is important for performing duties in a fast-changing world. Conclusion: Therefore, the integration of artificial intelligence in the Law for Training Development Course in the Non-Commissioned Officer Student Program is important to enhance skills in analytical thinking, problem-solving, and applying laws in real-life situations for non-commissioned officer students, as well as preparing them to deal with potential challenges in the digital era efficiently.